Nutritional Knowledge and Behavior of Adults: Their Relations with Sociodemographic Factors - HAKLI, Gulperi; ASIL, Esma; UCAR, Asli; OZDOGAN, Yahya; YILMAZ, Mustafa Volkan; OZCELIK, Ayse Ozfer; SURUCUOGLU, Metin Saip; CAKIROGLU, Funda Pinar; AKAN, Lale S. (Pakistan Journal of Nutrition, 2016)
This cross-sectional study was carried out for the purpose of investigating the factors affecting nutritional knowledge and behaviors of adults and the relation between nutritional knowledge and these behaviors. The study population consisted of 1062 adults aged 18-65 who presented to health care centers (mean age was 37.6±11.7 years). Data was collected through a questionnaire. In both score types, participants with undergraduate and graduate degrees and the employed got the highest scores. The difference between the mean knowledge score according to age (p